Educational intervention for collecting sputum for tuberculosis: a quasi-experimental study - Amélia Nunes Sicsú; Julia Ignez Salem; Luciana Botinelly Mendonça Fujimoto; Roxana Isabel Cardozo Gonzales; Maria do Socorro de Lucena Cardoso; Pedro Fredemir Palha (Revista Latino-Americana de Enfermagem, 2016)
Abstract Objective: to evaluate the quality of the sputum sample before and after the Nursing guidance to patients. Methods: this is a quasi-experimental research design, single group type, before and after, non-randomized study. The study enrolled patients with suspected pulmonary tuberculosis, respiratory symptomatic patients for over three weeks, aged over 18 years, of both genders and without tuberculosis history in the last two years. The educational intervention consisted of individualized guidance on the collection of sputum sample, which was based on the guidelines of the Ministry of Health of Brazil and on the explanatory folder delivery. Results: in this study participated 138 patients with suspected pulmonary tuberculosis. The results showed significant increase of the samples with purulent particles, volume greater than 5 mL and increased rate of patients diagnosed with tuberculosis, after the educational intervention. Conclusion: it was shown that after the educational intervention, it was observed sputum samples with better quality, with satisfactory aspect and volume for the effectiveness of the bacilloscopic examination.